Liver-Directed Treatment Options Following Liver Tumor Recurrence: A Review of the Literature - Aquina, Christopher T.; Eskander, Mariam F.; Pawlik, Timothy M. (Frontiers in Oncology, 2022)
Recurrence following curative-intent hepatectomy for colorectal cancer liver metastasis, hepatocellular carcinoma, or cholangiocarcinoma is unfortunately common with a reported incidence as high as 75%. Various treatment modalities can improve survival following disease recurrence. A review of the literature was performed using PubMed. In addition to systemic therapy, liver-directed treatment options for recurrent liver disease include repeat hepatectomy, salvage liver transplantation, radiofrequency or microwave ablation, intra-arterial therapy, and stereotactic body radiation therapy. Repeat resection can be consider for patients with limited recurrent disease that meets resection criteria, as this therapeutic approach can provide a survival benefit and is potentially curative in a subset of patients. Salvage liver transplantation for recurrent hepatocellular carcinoma is another option, which has been associated with a 5-year survival of 50%. Salvage transplantation may be an option in particular for patients who are not candidates for resection due to underlying liver dysfunction, but meet criteria for transplantation. Ablation is another modality to treat patients who recur with smaller tumors and are not surgical candidates due to comorbidity, liver dysfunction, or tumor location. For patients with inoperable disease, transarterial chemoembolization, or radioembolization with Yttrium-90 are liver-directed intra-arterial therapy modalities with relatively low risks that can be utilized. Stereotactic body radiation therapy is another palliative treatment option that can provide a response and local tumor control for smaller tumors.